2020
DOI: 10.1002/mc.23199
|View full text |Cite
|
Sign up to set email alerts
|

PCAT6 mediates cellular biological functions in gastrointestinal stromal tumor via upregulation of PRDX5 and activation of Wnt pathway

Abstract: Gastrointestinal stromal tumor (GIST) is a common mesenchymal tumor in the gastrointestinal tract. Prostate cancer associated transcript 6 (PCAT6) is a long noncoding RNA (lncRNA) and plays a pivotal role in tumor formation. Present study was designed to explore the function of PCAT6 in GIST. Ki67 staining, colony formation and trypan blue staining assays revealed that PCAT6 boosted GIST cell proliferation but inhibited cell apoptosis. Also, sphere formation assay and Western blot uncovered the promoting role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Previously, prostate cancer-associated transcript 6 (PCAT6) has been identified as an lncRNA involved in the regulation of lung cancer progression (14). Subsequently, several studies have highlighted the abnormal expression of lncRNA PCAT6 in various malignant tumors, including gastrointestinal stromal tumor, colon cancer and osteosarcoma, suggesting that PCAT6 may play an essential role in tumor progression (15)(16)(17). Although the oncogenic roles of PCAT6 have been demonstrated in several tumors,…”
Section: Introductionmentioning
confidence: 99%
“…Previously, prostate cancer-associated transcript 6 (PCAT6) has been identified as an lncRNA involved in the regulation of lung cancer progression (14). Subsequently, several studies have highlighted the abnormal expression of lncRNA PCAT6 in various malignant tumors, including gastrointestinal stromal tumor, colon cancer and osteosarcoma, suggesting that PCAT6 may play an essential role in tumor progression (15)(16)(17). Although the oncogenic roles of PCAT6 have been demonstrated in several tumors,…”
Section: Introductionmentioning
confidence: 99%
“…lncRNA PCAT6 is a lncRNA that has been reported to be upregulated in osteosarcoma and colorectal cancer (26,27) and has emerged as a critical regulator in tumorigenesis and cancer progression. For example, Bai et al (28) have demonstrated that PCAT6 promotes gastrointestinal stromal tumor cell proliferation and stemness, but inhibits apoptosis through the ceRNA mechanism and the activation of the Wnt signaling pathway. Ma et al (14) have reported that PCAT6 facilitates the proliferation, migration and cisplatin resistance of cervical cancer cells and impedes their apoptosis via the PCAT6/miR-543/zinc finger E-box-binding homeobox 1 axis.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in silico pathway and network analyses implicated the hypoxia-inducible factor 1 pathway as a mediator of imatinib resistance. The role of the lncRNA prostate cancer-associated transcript 6 (PCAT6) was examined by Bai et al [131]. First, PCAT6 was found to be upregulated in GIST in comparison with adjacent non-cancerous tissue.…”
Section: Additional Non-coding Rnas In Gastrointestinal Stromal Tumorsmentioning
confidence: 99%
“…Finally, miRNAs associated with imatinib resistance [30,110,114,115,[117][118][119] may be used to signal evolving imatinib resistance enabling early clinical intervention. Interestingly, lncRNAs have also been identified that could be used for diagnostic purposes [129,131,133] or are specifically linked to high-risk/advanced GIST [108,122,123,125,128] and imatinib resistance [126,127,130]. However, more research is necessary to select the miRNA classifiers that are most promising for validation in prospective clinical studies.…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation